2012
DOI: 10.3758/s13428-012-0189-x
|View full text |Cite
|
Sign up to set email alerts
|

An action video clip database rated for familiarity in China and Germany

Abstract: Stimulus material for studying object-directed actions is needed in different research contexts, such as action observation, action memory, and imitation. Action items have been generated many times in individual laboratories across the world, but they are used in very few experiments. For future studies in the field, it would be worthwhile to have a larger set of action stimulus material available to a broader research community. Some smaller action databases have already been published, but those often focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…The current Experiment 1 is effectively a preliminary experiment conducted on behalf of researchers who wish to use the NOUN Database. This is valuable because obtaining and selecting experimental stimuli is often a highly time-consuming phase of the research process (Dan-Glauser & Scherer, 2011; see also Umla-Runge, Zimmer, Fu, & Wang, 2012). Even using 3D rendering software can take time to learn and be expensive.…”
Section: Why Use the Noun Database?mentioning
confidence: 99%
“…The current Experiment 1 is effectively a preliminary experiment conducted on behalf of researchers who wish to use the NOUN Database. This is valuable because obtaining and selecting experimental stimuli is often a highly time-consuming phase of the research process (Dan-Glauser & Scherer, 2011; see also Umla-Runge, Zimmer, Fu, & Wang, 2012). Even using 3D rendering software can take time to learn and be expensive.…”
Section: Why Use the Noun Database?mentioning
confidence: 99%
“…Videos were taken from an online database of hand-related actions [ 57 ] and edited using iMovie [ 58 ] to create a 2-s stimulus representing each action. Subsequently, screenshots of the videos were taken to create corresponding pictures for each action (see Figure 1 for an example).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, screenshots of the videos were taken to create corresponding pictures for each action (see Figure 1 for an example). Of the 1074 video clips of actions that were available in the online database created by Umla-Runge and colleagues [ 57 ], 22 biologically-relevant action verb video clips were initially selected as stimuli for this study based on three criteria—recognizable action in picture and video format, name agreement, and similar psycholinguistic criteria of concreteness, familiarity, imageability, and frequency. First, the researchers chose actions which could be identified from a still shot of the video using three independent reviewers.…”
Section: Methodsmentioning
confidence: 99%
“…However, in a second validity analysis we compared our results with the norms provided by Hinojosa, Rincón-Pérez, et al (2016b), the only published study that has collected SER ratings in Spanish to date, and a correlation of r = .818 (p < .001) was found for a set of 471 shared words. Although translation issues are the most likely explanation for the difference between the correlations of our norms with those from the aforementioned SER studies in English and Spanish, cross-cultural differences in SER ratings should also be considered and explored in more detail in the future, since a few normative studies have found substantial differences in normative measures as a function of culture (e.g., Umla-Runge, Zimmer, Fu, & Wang, 2012;Yoon et al, 2004).…”
Section: Reliability and Validitymentioning
confidence: 99%